2021
DOI: 10.31288/oftalmolzh202156470
|View full text |Cite
|
Sign up to set email alerts
|

Neopterin level in the anterior segment of the eye in induced uveitis with ocular hypertension when treated by dipeptide carnosine

Abstract: Background:We have previously demonstrated that the course of inflammatory process was significantly more severe in eyes with anterior uveitis with ocular hypertension (OHT) than in those with anterior uveitis with normal intraocular pressure (IOP), which was largely due to a more marked activation of enzymes producing active oxygen as well as peroxidative processes in uveal structures of experimental animals. Aside from oxidative stress characteristics, our attention has been drawn to neopterin as a potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Moreover, we have previously reported that carnosine instillation in the conjunctival sac signiticantly reduced neopterin levels in uveal tract tissue, aqueous humor and tear samples from the rabbit eye with experimental anterior uveitis plus OHT, indicating a reduction in inflammation in the anterior segment of the eye [20,44].…”
Section: Discussionmentioning
confidence: 90%
“…Moreover, we have previously reported that carnosine instillation in the conjunctival sac signiticantly reduced neopterin levels in uveal tract tissue, aqueous humor and tear samples from the rabbit eye with experimental anterior uveitis plus OHT, indicating a reduction in inflammation in the anterior segment of the eye [20,44].…”
Section: Discussionmentioning
confidence: 90%